PENGARUH BOOK TAX DIFFERENCES TERHADAP PERUBAHAN LABA - Nur Aini Rosanti; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2013)
This study aims to examine the influence of book tax differences toward earning changes.Earnings change is calculated by subtracting the net income one period ahead with current netincome and then divided by the current net income. Independent variables used in this study istemporary differences and permanent differences which are proxy of book tax differences, while thedependent variable is earnings change.The population of this study is the manufacturing companies listed in Indonesia StockExchange in 2008-2010. Sampling conducted with a random sampling technique. Based randomsampling method, the sample obtained a total of 31 companies. The method of analysis that wasused to test the independent variables influence the dependent variable is the multiple regression.The results showed that permanent differences has no significant affect toward earningschange. Temporary differences has no significant affect toward earnings change.